2017
DOI: 10.1182/bloodadvances.2017007013
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic ethnicity is associated with younger age at presentation but worse survival in acute myeloid leukemia

Abstract: Key Points SEER data and a Bronx validation cohort demonstrate that Hispanics present with AML at younger age but have shorter survival than whites. Increased frequency of high-risk mutations in Hispanics provides a potential biologic explanation for poorer outcomes in Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Ethnic and racial disparities have been described in the outcomes of hematological malignancies such as acute leukemia and attributed to a combination of biological and non-biological factors [ 13 , 14 ]. Age-adjusted overall survival of AML was reported to be worse in Hispanics compared with whites [ 11 ]. It was demonstrated that cytogenetic abnormalities are common in AML and are associated with a significant prognostic impact on AML patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ethnic and racial disparities have been described in the outcomes of hematological malignancies such as acute leukemia and attributed to a combination of biological and non-biological factors [ 13 , 14 ]. Age-adjusted overall survival of AML was reported to be worse in Hispanics compared with whites [ 11 ]. It was demonstrated that cytogenetic abnormalities are common in AML and are associated with a significant prognostic impact on AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…AML appears less common in Hispanics when compared with whites; however, acute promyelocytic leukemia (APL) appears comparatively more common in Hispanics when compared with whites [ 16 ]. It was revealed that there were significantly higher mutation rates of ASXL1 and TET2 genes in Hispanic AML patients than in white AML patients, which may provide a biological explanation for the inferior outcomes of AML in Hispanics [ 11 ]. The varied distribution of acute leukemia among these ethnic groups suggests that host susceptibility factors are critical determinants of disease in one group, but not in another group [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of these favorable markers does not translate into improved clinical outcomes (Darbinyan et al, 2017;Kirtane and Lee, 2017;Patel et al, 2013;Patel et al, 2012;Patel et al, 2015). Additional biological factors contributing to this health disparity include mutations in CEBPA, RUNX1, GATA2, AML1-ETO, U2AF1, and KIT, which was observed at a higher prevalence in Hispanic versus NHWs.…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%